Memórias de professores de ciências e biologia no início de carreira docente: conflitos e tensões - OLIVEIRA, Sônia Maria Maia (2004)
The present work deals with a research narrative delineated from elements gifts in the memories of six professors of Sciences and Biology, where I search to explicit, for the reflexive inquiry, conflicts and tensions in the beginning of its careers as professors. I search to evedenciar as it was this beginning, considering for this the three first years of performance. The inquiry was carried through in a public school of Belém-Pará. having been the done choice of intentional form, in virtue of my performance as teacher of Practical of Education, in the context where the citizens act, what also it facilitated my insertion for this inquiry. The citizens of my research are egresses of the Course of Full Licenciatura in Biological Sciences of the Federal University of Pará and acts or had acted effectively in classroom in the levels basic, average and superior. The depositions had been gotten by means of half-structuralized interview, being organized in true of analysis axles, from that I argue the problem: Difficulties of personal order, the referring ones to the pertaining to school environment, and those on ones to the educational system. The gotten results had been excellent so that let us can reflect in this context diverse implications with regard to initial insertion of the professor in the career. These implications require innovative deep reflections and face the difficulties that had been found in the ambit of the analyzed axles. For being formadora teacher, I feel myself co-responsible for the initial formation of professors and I consider myself to search mechanisms essential to minimize these and other difficulties lived deeply for the professors in the beginning of its teaching career, since it is in the beginning of career that the person perceives how much it becomes necessary to learn to surpass the diverse difficulties found in the way.